2019
DOI: 10.1175/jhm-d-18-0158.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Continuous Characterization of Forest Canopy Structure and Subcanopy Irradiance Derived from Handheld Radiometer Surveys

Abstract: Small-scale variations in radiative transfer through forest canopies are strongly linked to canopy structural heterogeneity. To date, upscaling of radiative transfer parameterizations developed at the point scale is hampered by (i) poor representation of canopy structure variability and (ii) limited spatially explicit subcanopy irradiance data to assess the performance of radiative transfer schemes at typical resolutions of land surface models. This study presents a novel approach for efficient in situ charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Improved observational systems and resulting data sets constitute the key novelty of our model evaluation approach. Malle et al (2019) and Mazzotti, Malle, et al (2019) already demonstrated the utility of these mobile systems for generating spatially and temporally resolved radiation data to complement earlier studies (Lawler & Link, 2011; Sicart et al, 2004). In the context of this work, additional benefits arise from combining observations of irradiance with the acquisition of air and snow surface temperature data.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Improved observational systems and resulting data sets constitute the key novelty of our model evaluation approach. Malle et al (2019) and Mazzotti, Malle, et al (2019) already demonstrated the utility of these mobile systems for generating spatially and temporally resolved radiation data to complement earlier studies (Lawler & Link, 2011; Sicart et al, 2004). In the context of this work, additional benefits arise from combining observations of irradiance with the acquisition of air and snow surface temperature data.…”
Section: Discussionmentioning
confidence: 91%
“…The areas span varying climatic conditions and forest types, with a focus on conifer species. In Switzerland, the field sites in the area near Davos Laret have hosted numerous forest snow research projects, as documented in Malle et al (2019), Mazzotti, Malle, et al (2019), Moeser et al (2014), Moeser et al (2015), Webster and Jonas (2018), and Webster et al (2016b). The forest in Laret primarily consists of Norway spruce, including both new and old growth (trees up to 45 m tall).…”
Section: Study Areas and Time Framementioning
confidence: 99%
See 2 more Smart Citations
“…They include: Leaf area index (LAI): the dimensionless ratio of one‐sided needle leaf area per unit ground area (e.g., Chen et al, ). Note that in some literature vegetation area index (VAI) is used instead, which may also include other vegetation elements such as stems and branches. Sky view fraction (V F ): the visible portion of sky in the hemispherical field of view seen from a specific point, weighted by the sine of elevation angle (e.g., Essery, Pomeroy, et al, ). Canopy cover fraction (CC): the ratio of area covered by the vertical projection of the canopy relative to ground area in a two‐dimensional bounding box (e.g., Mazzotti, Malle, et al, ). Mean canopy height (mCH): the average height of the canopy elements in a two‐dimensional bounding box (e.g., Varhola & Coops, ). …”
Section: Methodsmentioning
confidence: 99%